2012
DOI: 10.1161/str.43.suppl_1.a2467
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2467: Factors Affecting the Discharge Disposition after Stroke

Abstract: Background and Purpose: Stroke is the third leading cause of death and is the leading cause of adult disability in Taiwan. Stroke patients are frequently in need of professional care and assistance in activities of daily living. Home care may not provide adequate support for some of the disabled stroke patients. Discharge disposition after stroke is an important long-term care issue affecting the families and societies in every country, developed or developing. We have made analyses of more than 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the present study, the proportion of rehabilitants returning to community was in the range of previous studies on community discharge after acute severe stroke varying from 45% 20 to 58% 18,30 to 66%, 19 in very severe stroke 36%. 18 In accordance with our results, high age 7 -9,17,19,31,32 with rare exceptions, 33,34 and high stroke severity and disability on admission to acute care (NIHSS) and on admission to subacute rehabilitation (FIM or Barthel Index) 11,13,14,17 have been found to be the most important predictors of institutionalization after acute stroke care, after rehabilitation, and at 3 months after stroke. Likewise, older age 35 and more severe stroke 35,36 at acute discharge 36 and in the first month and 3 or more months post-stroke 35 have also been found to be significant predictors for overall poor stroke outcome, functional ability, and post-stroke disposition after rehabilitation.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the present study, the proportion of rehabilitants returning to community was in the range of previous studies on community discharge after acute severe stroke varying from 45% 20 to 58% 18,30 to 66%, 19 in very severe stroke 36%. 18 In accordance with our results, high age 7 -9,17,19,31,32 with rare exceptions, 33,34 and high stroke severity and disability on admission to acute care (NIHSS) and on admission to subacute rehabilitation (FIM or Barthel Index) 11,13,14,17 have been found to be the most important predictors of institutionalization after acute stroke care, after rehabilitation, and at 3 months after stroke. Likewise, older age 35 and more severe stroke 35,36 at acute discharge 36 and in the first month and 3 or more months post-stroke 35 have also been found to be significant predictors for overall poor stroke outcome, functional ability, and post-stroke disposition after rehabilitation.…”
Section: Discussionsupporting
confidence: 88%
“…All other variables studied except for hypertension, that is, sex, diabetes mellitus, heart diseases, stroke history, snoring, lack of family member as a caregivers, and stroke types (main artery atherosclerosis or hemorrhage) were also found to be independent, but more modest predictors for institutionalization and gender difference disappeared in multiple logistic regression model. 17 We found that for every 1 point increase in NIHSS score on admission to rehabilitation the odds of returning home on average 2 to 3 months after stroke onset decreased with 16.1% and for every 1 year increase in age the odds of being discharged home decreased with 5.4%. Together NIHSS score and age explained 62.9% of community discharge and 74.4% of institutional discharge, the overall predictive accuracy being 69.2%.…”
mentioning
confidence: 67%
See 3 more Smart Citations